Stress resilience in male adolescents and subsequent stroke risk: cohort study. Issue 12 (28th March 2014) - Bergh, Cecilia; Udumyan, Ruzan; Fall, Katja; Nilsagård, Ylva; Appelros, Peter; Montgomery, Scott
Abstract : Objective: Exposure to psychosocial stress has been identified as a possible stroke risk, but the role of stress resilience which may be relevant to chronic exposure is uncertain. We investigated the association of stress resilience in adolescence with subsequent stroke risk. Methods: Register-based cohort study. Some 237 879 males born between 1952 and 1956 were followed from 1987 to 2010 using information from Swedish registers. Cox regression estimated the association of stress resilience with stroke, after adjustment for established stroke risk factors. Results: Some 3411 diagnoses of first stroke were identified. Lowest stress resilience (21.8%) compared with the highest (23.7%) was associated with increased stroke risk, producing unadjusted HR (with 95% CIs) of 1.54 (1.40 to 1.70). The association attenuated slightly to 1.48 (1.34 to 1.63) after adjustment for markers of socioeconomic circumstances in childhood; and after further adjustment for markers of development and disease in adolescence (blood pressure, cognitive function and pre-existing cardiovascular disease) to 1.30 (1.18 to 1.45). The greatest reduction followed further adjustment for markers of physical fitness (BMI and physical working capacity) in adolescence to 1.16 (1.04 to 1.29). The results were consistent when stroke was subdivided into fatal, ischaemic and haemorrhagic, with higher magnitude associations for fatal rather than non-fatal, and for haemorrhagic rather than ischaemic stroke. Conclusions: Stress susceptibility and, therefore, psychosocial stress may be implicated in the aetiology of stroke. This association may be explained, in part, by poorer physical fitness. Effective prevention might focus on behaviour/lifestyle and psychosocial stress.